MOBILIZATION POTENTIAL OF PATIENTS WITH LYMPHOMAS AND MULTIPLE MYELOMA INVOLVED IN ASCT - Stančev, Katarina (Medicinski podmladak, 2020)
Abstract: Introduction: High-dose chemotherapy by following autologous stem cell transplant (ASCT) is a standard treatment of multiple myeloma (MM), relapse of Hodgkin’s lymphoma (HL) and non-Hodgkin’s lymphomas (NHL). Monitoring of clinical and biochemical characteristics, as well as post-transplant parameters points to the importance of mobilization potential. Aim: To evaluate the association of early recovery of neutrophil granulocytes ≥0.5 x 109/L after 11 days of transplantation (ANC500_11), platelets ≥20 x 109/L after 13 days of transplantation (PLT20_13) with clinical stage, duration of mobilization, as well as number of mobilization attempts, therapeutic response and dose CD34+ cells in the apheresis product. Material and Methods: The retrospective study included 100 patients, of which 51 patients with MM, 27 with NHL and 22 with HL, in the period from November 2015, ending December 2018. Results: The average age of the patient was 49.8 years. According to the DSS, 69% were in IIIA, while 12.5% of patients were in the IIIB clinical stage. According to the Ann-Arbor staging 92% patients were in the II or III clinical stage. The average number of CD34+ cells in the apheresis product was 8.3x106/kgBM. In the first attempt mobilization on average was 6.49±1.3 days. Engraftment is most often detected during the 11th day. In 78% of patients, mobilization was successful in the first attempt (≥2.0x106/kgBM) among which 86% were MM and 69,4% of lymphomas (p<0.05). The impacts of age, the number of CD34+ cells in the peripheral blood and the duration of the mobilization did not show a significant difference (p>0.05) in relation to the recovery of ANC500_11 and PLT20_13. Conclusion: Satisfactory CD34+ cellular yield can be provided in the first mobilization attempt in most of the patients with usage of GCS-F, while in the further mobilization attempts plerixafor was used. Also, age, therapeutic response and different therapeutic protocols have no impact on ANC500_11 and PLT20_13.